Phytochemical studies and biological activities of parmotrema sulphuratum - Soo, Wai See (Universiti Malaysia Sarawak (UNIMAS), 2015)
The aim of this study was to determine the secondary metabolites, cytotoxic activity and termiticidal activity of lichen Parmotrema sulphuratum, which was collected from Borneo Highland, Sarawak. Phytochemical examination on the dichloromethane extract of the lichen gave percentage yield of 16.66 % and led to the isolation and characterization of atraric acid. Column Chromatography method has been developed to fractionate the dichloromethane crude into several fractions and purify them by using the 20 cm х 20 cm Preparative TLC plate. The pure compound was subjected to Gas Chromatography Flame Ionization Detector to determine the purity. The structure of atraric acid was elucidated by Gas Chromatography-Mass Spectrometry, 1H and 13C Nuclear Magnetic Resonance Spectroscopy and Fourier Transform Infrared. The components of the lichen were identified based on spectral data and comparison with published information. Bioassay was carried out on Artemia salina and Rhinotermes sp. and results indicate that the all the extracts do not exhibit cytotoxic activity and termiticidal activity.